2018
DOI: 10.1109/jbhi.2017.2688239
|View full text |Cite
|
Sign up to set email alerts
|

DREAMER: A Database for Emotion Recognition Through EEG and ECG Signals From Wireless Low-cost Off-the-Shelf Devices

Abstract: In this paper, we present DREAMER, a multimodal database consisting of electroencephalogram (EEG) and electrocardiogram (ECG) signals recorded during affect elicitation by means of audio-visual stimuli. Signals from 23 participants were recorded along with the participants self-assessment of their affective state after each stimuli, in terms of valence, arousal, and dominance. All the signals were captured using portable, wearable, wireless, low-cost, and off-the-shelf equipment that has the potential to allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
420
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 697 publications
(429 citation statements)
references
References 37 publications
3
420
2
4
Order By: Relevance
“…The output from both streams is then concatenated before passing through a dense layer to output a regression estimate for valence,ŷ. higher accuracy across both datasets than previously reported [40], [43] (Table II).…”
Section: Resultsmentioning
confidence: 42%
See 3 more Smart Citations
“…The output from both streams is then concatenated before passing through a dense layer to output a regression estimate for valence,ŷ. higher accuracy across both datasets than previously reported [40], [43] (Table II).…”
Section: Resultsmentioning
confidence: 42%
“…This allowed us to exploit existing high-quality ECG datasets for this study. We developed an end-to-end neural network capable of modelling temporal structure in the IBI time series, which outperformed previous classifiers on this task [40], [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, those studies that have explored unimodal heartbeat models for emotion detection tend to ignore temporal structures of the signal. Instead, they use 'static' classification methods that analyse global features of the input time-series, such as Naive Bayes (NB), [16], [18], linear discrimant analysis (LDA) [22], and support vector machine (SVM) [15], [19], [21]. A summary of these studies can be found in Table I.…”
Section: Related Workmentioning
confidence: 99%